Effect of Natural Fe2O3 Doping on Performance of Lithium Phospate Ceramic Glass as Secondary Battery Cathode - Mukhtar Effendi; Dina Rahmawati; Wahyu Tri Cahyanto; Wahyu Widanarto (Molekul, 2017)
Natural Fe2O3 doped lithium phosphate Ceramic-glass was made by glass route method at 900 oC with the composition of 5Li2CO3:15ZnO : x Fe2O3: (80 – x) P2O5 where x =  0; 0.5; 1.5 (in mol percent). Thermal stability of sample was studied through determination of glass temperature Tg and crystal temperature Tc. XRD pattern and LCR meter measurement were carried out to determine phase, structure and ionic conductivity of the ceramic-glass samples. LiFePO4 was formed at 1.5% addition of Fe2O3. Ionic conductivity rise up by the increasing Fe2O3 concentration. The highest electric conductivity is 8,42 x 10-4 S/cm which was obtained at 1.5% addition of Fe2O3